When the reckoning comes : a novel - McQueen, LaTanya (Harper Perennial, 2021)
"A haunting novel about a black woman who returns to her hometown for a plantation wedding and the horror that ensues as she reconnects with the blood-soaked history of the land and the best friends she left behind"--